Supracutaneous plating in tibial metadiaphyseal fractures with compromised soft tissue using LCP as an external fixator - Kalia, Sandeep; Sharma, Shalini; Sehgal, Manik; Kanwar, Sachin (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2019)
Introduction: Tibial meta-diaphysealfractures are challenging injuries because of subcutaneous anteromedial surface of bone and frequent soft tissue complications. Ideal management requires stable fixation with minimal soft tissue handling. Locking compression plate (LCP) applied as an external fixator fulfills these criteria and can be an important tool in the armamentarium of an orthopaedic surgeon. Objective of the study is to evaluate the result of this technique. Methods: 23 patients with meta-diaphyseal fractures of tibia with compromised soft tissue treated by this technique were evaluated retrospectively interms of union, maintenance of reduction, complications and final outcome using KSS (Knee society scoring) for proximal fractures and AOFAS (AO Ankle and Foot scoring) for distal fractures. Average follow up duration was 9.4 months (6-14 months). Results: There were fifteen males, eight females with fourteen open fractures and nine cases of closed fractures with tscherne grade 2 or 3 soft tissue injury. Five fractures were in proximal tibia and eighteen were in distal tibia, all fractures united with an average of 21.7 weeks period maintaining acceptable reduction. There were 3 cases of infection, one deep and two superficial treated successfully by debridement and antibiotics. Average knee society scores were 74 and 78.6 for open and close proximal metadiaphyseal fractures respectively. Average AOFAS scores were 81.9 and 84 for open and close distal tibial metadiaphyseal fractures respectively. Conclusion: we found this technique to be more biological, simple to do surgery, effective in maintaining reduction till union, more patient friendly in comparison to traditional large, bulkyfixators and with minimal complications.